Exploring user experiences of clinicians engaged with the digital healthcare interventions across the referral and university teaching hospitals in Nigeria: a qualitative study - Onyeabor, Uchechukwu Solomon; Onwuasoigwe, Okechukwu; Okenwa, Wilfred Okwudili; Schaaf, Thorsten; Pinkwart, Niels; Balzer, Felix (Frontiers in Digital Health, 2025)
IntroductionGiven that Nigeria and several developing countries are still at the early stage of digital healthcare interventions adoption (like the use of electronic health records systems) there is scarcity of research/empirical reports investigating the overall user experiences of clinicians, the doctors and the nurses who are or who had been practically engaged with the use of these new digital healthcare support implementations that had engendered new culture across their care delivery facilities. The referral and university teaching hospitals in Nigeria numbering over 166 and scattered across over 37 states of the federation and the Federal Capital Territory (FCT) make up a strategic component of Nigeria's healthcare ecosystem. This research was therefore designed and restricted to clinicians who had used these systems so as to explore their experiences with these systems and possibly unveil any challenges/limitations that can bedevil successful and sustainable acquisition of digital healthcare intervention programmes and projects across referral and university teaching hospitals in the Southeastern Region of Nigeria; and could also hamper any future implementations.MethodThis study was designed in a manner that allows the clinicians the liberty to conveniently express in writing (via comments) issues, challenges and concerns that they had perceived, encountered or experienced bedevilling electronic health record adoption and use across their care facilities. So a structured interview method was chosen by the research team (after due considerations) as fitting the research context. This (structured interview) was therefore designed and targeted at about 400 clinical participants, including the doctors and the nurses from three select referral and university teaching hospitals in the Southeastern Region of Nigeria (a federal, state, and national specialist referral hospital).ResultOut of the 400 clinicians who were targeted in the survey, 326 of them practically responded to the interview questions. The outcome showed the clinicians willingly exposing several issues and challenges that had stifled electronic health record adoption across the hospitals. Issues identified were categorized into themes including challenges bordering on lack of political will on the part of hospital administration; lack of computer/digital/EHR literacy; poor and often lack of comprehensive training on the workings of EHR; poor maintenance culture; poor EHR system design, poor implementation and use-based struggles and challenges; infrastructure issues, system breakdown and network challenges etc were reported.ConclusionThe outcome of this investigation has profoundly exposed practical issues that had hitherto stifled and often suffocated electronic health record implementation projects across referral and university teaching hospitals in Nigeria. And given the strategic importance of these hospitals in Nigeria healthcare ecosystem, conscious and concerted efforts must be made to address them.